1999
DOI: 10.1097/00007632-199911150-00004
|View full text |Cite
|
Sign up to set email alerts
|

Operative Results of Canal-Expansive Laminoplasty for Cervical Spondylotic Myelopathy in Elderly Patients

Abstract: The severity of the clinical picture and the duration of symptoms influenced the outcome of the operation. Despite the advanced age of some patients (> 80), the operation increased the chance of recovery from the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
2
7

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(64 citation statements)
references
References 12 publications
2
53
2
7
Order By: Relevance
“…Some studies have reported that the elderly tended to have a longer duration of symptoms, poorer surgical outcome and more cephalic levels involved [4,5,7,10]. However, other authors have not demonstrated any differences in the duration of symptoms [3,10] or surgical outcome [4,8] between elderly and younger patients. These discrepancies may be attributed to their definitions of the term elderly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reported that the elderly tended to have a longer duration of symptoms, poorer surgical outcome and more cephalic levels involved [4,5,7,10]. However, other authors have not demonstrated any differences in the duration of symptoms [3,10] or surgical outcome [4,8] between elderly and younger patients. These discrepancies may be attributed to their definitions of the term elderly.…”
Section: Introductionmentioning
confidence: 99%
“…Many papers describe cervical myelopathy in elderly patients [3][4][5][6][7][8][9][10]; however, definitions of the term elderly have varied from over 65 years [7,8,10] to over 70 years [3,4,9] and to over 75 years [5,6]. Some studies have reported that the elderly tended to have a longer duration of symptoms, poorer surgical outcome and more cephalic levels involved [4,5,7,10].…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] The following factors have been reported to influence postoperative results: duration of the disease, severity of myelopathy, intramedullary signal intensity changes on MRI and crosssectional area of the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…The reported long-term results of this procedure have been considered satisfactory. [1][2][3][4][5][6][7][8][9][10][11][12] However, a few patients have exhibited late neurological deterioration after good recovery immediately after surgery. Numerous studies have been performed to elucidate the causes of late deterioration after this procedure.…”
Section: Introductionmentioning
confidence: 99%
“…7,10,12,13 Although spondylotic changes including spur formation and disc herniation have occasionally developed in operated segments after laminoplasty, few patients have required additional surgery for treatment of relapse of neurological deficits. [1][2][3][4][6][7][8][9][10][11][12] It is believed that the spinal cord is rarely compressed by spondylotic changes since it is shifted posteriorly in the enlarged spinal canal after laminoplasty.…”
Section: Introductionmentioning
confidence: 99%